Occurrence of Autoimmune Thyroid Dysfunction in Juvenile SLE - Humaira Bibi, Afsheen Batool Raza, Farrah Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To define the occurrence of autoimmune thyroid dysfunction and its type i.e. sub-clinical hypothyroidism, hypothyroidism and hyperthyroidism in juvenile SLE. Study design: Cross-sectional study. Place and duration: The study was held at the rheumatology ward of the Children’s hospital and the Institute of Child Health, Lahore from1st November 2019 to 30th April 2021. Sample Technique: Non probability consecutive sampling Material and methods: Inclusion Criteria had American college of rheumatology classification criteria for SLE filled by both female and male patients of 2-16 years. Consent was taken and all the data was written on pre designed proforma. Demographic data like age, gender and relevant history and examination was done to diagnose hypo or hyperthyroidism. Thyroid antibodies, 3 to 5 ml of venous blood for thyroid function tests of all patients were sent in laboratory and results were interpreted accordingly. Thyroid dysfunction and its types were labeled accordingly. Results: In the present study, 55.56% (n=50) were between 9-16 years of age whereas 44.44% (n=40) were between 2-8 years of age, out of 90 cases. Mean and Sd. was calculated as 9.73+3.29 years, 30% (n=27) were male while 70%(n=63) were females, frequency of autoimmune thyroid dysfunction was recorded in 28.89%(n=26), frequency of type of autoimmune thyroid dysfunction was recorded as 10%(n=9) for sub-clinical hypothyroidism, 11.11%(n=10) for Hypothyroidism and 7.78%(n=7) for hyperthyroidism. Conclusion: It is concluded that the occurrence of autoimmune thyroid dysfunction is higher in our population, however, some-other studies are required to validate our findings.